ASSA13-15-9 A Meta-Analysis of Percutaneous Coronary Intervention For Chronic Total Coronary Occlusions Recanalization. (29th April 2013) - Long, Jiang; Xiaoshu, Cheng; Renqiang, Yang; Yingli, Fan; Rui, Zhan; Lijuan, Hu
Abstract : Background: Despite advances in procedural techniques and expertise, PCI for CTO recanalization in select patients remains a challenge. Objective: To perform an evaluation (meta-analysis) on short-term and long-term prognosis of percutaneous coronary intervention (PCI) for patients with chronic total occlusions (CTO) recanalization. Methods: Data sources included published studies from a search of PUBMED, ELSEVIER, and CLINICAL.COM from January 2000 to July 2012. Selected studies were either observational studies or randomised clinical trials that compared PCI treatment of CTO recanalization to medical management. The endpoints were analysed using pooled estimates for death, myocardial infarction (MI), coronary artery bypass surgery (CABG), angina symptoms, repeat revascularization, and major adverse cardiac events (MACE). Results: Sixteen observational studies comparing outcomes after failed or successful CTO recanalization with PCI were included in the current analysis. Collectively, these studies enrolled 10, 256 patients who were observed at an average follow-up period of 5 years. Patients with successful CTO recanalization demonstrated significantly reduced rates of all-cause death (P < 0.00001), cardiac death (P < 0.00001), MACE (P < 0.0001), MI (P = 0.003), subsequent CABG (P < 0.00001), and long-term repeat revascularization (P = 0.03). In addition, successful CTO improved quality of life (P = 0.0001), reduced both MACE (P < 0.00001) and mortality (P = 0.004) in patients with multivessel disease, and resulted in a lower death rate in patients with single vessel disease (SVD; P = 0.02); although there was no difference in MACE events in patients with SAD. Conclusions: PCI should be considered an effective option for the patients with CTO lesions.